Magnetic properties of sediments of the Red River: Effect of sorting on the source‐to‐sink pathway and its implications for environmental reconstruction. (2nd February 2016) - Nguyen, Thi Thu Hien; Zhang, Weiguo; Li, Zhen; Li, Jie; Ge, Can; Liu, Jinyan; Bai, Xuexin; Feng, Huan; Yu, Lizhong
Abstract: We conducted a mineral magnetic study of river bank and subaqueous delta sediments from the Red River, in order to examine the role of sedimentary sorting on the variation of sedimentary magnetic properties from source to sink. The magnetic mineralogy mainly consists of magnetite and hematite. Bulk sediment particle‐size variations have a strong influence on magnetic properties, with the frequently used magnetic parameters χfd %, χARM, χARM /χ, and χARM /SIRM exhibiting positive correlations with the <4 µm fraction, while S‐ratios are negatively correlated with this fraction. Compared with river bank sediments and shallow shoreface (<5 m water depth) sediments, sediments from the deeper (>5 m water depth) part of the subaqueous delta have lower χ and SIRM values, a finer ferrimagnetic grain‐size and higher proportions of hematite, consistent with selective loss of coarse ferrimagnetic grains on the source‐to‐sink pathway. We suggest that variations in magnetic properties in response to particle‐size compositions and therefore depositional environment changes should be carefully addressed when magnetic proxies such as χARM /SIRM are used in the study of coastal and marine environmental changes (e.g., sea‐level change). In such cases, the combined use of magnetic properties and geochemical indicators, such as Al/Ti ratio, may provide better results for paleoenvironmental reconstruction. Key Points: Magnetic properties of sediments on the source to sink pathway of the Red River are studied Magnetic grain‐size and mineralogy indicators are sensitive to sediment sorting Magnetic proxies of environmental change are more reliable when used with geochemical indicators